LEKSIKON BUDAYA DALAM FOLKLOR LISAN MASYARAKAT DAYAK KEBAHAN - Yushar Mogarami; Patriantoro Patriantoro; Agus Syahrani (Universitas Tanjungpura, 2022)
The cultural lexicon is a component of language communication that contains the meaning and use of words in language. This cultural lexicon obtained from oral folklore found in the Dayak Kebahan Community (MDK) is generally something that is closely related in an oral tradition that is still being carried out from one generation to the next from generation to generation by the Dayak Kebahan Community. At present, many people do not understand about the real Dayak oral folklore culture and what is contained in it. This is the reason the researcher chose oral philchlor in the Dayak Kebahan community. The wisdom of the oral tradition and the diversity of Dayak Kebahan customs are distinct characteristics from other Dayak sub-tribes. The research was conducted in Nusa Kenyikap Village, Belimbing District, Melawi Regency, which is the residence of the indigenous Dayak Kebahan community. This study covers the form of lingual units, , lexicon, lexical meaning, cultural meaning and plans for implementing the research on oral folklore of the Dayak Kebahan Community towards learning in schools. The method used in this research is a descriptive method with a qualitative research form. The technique used in this research is observation, face-to-face technique, recording technique and note-taking technique, while the tools used are a list of questions and documentation equipment. Based on the results of the analysis, there are eight classifications of the Dayak Kebahan cultural lexicon.